PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECKS TERHADAP KEMAMPUAN KOMUNIKASI DAN HASIL BELAJAR PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN SISWA KELAS XI IPA SMA NEGERI 1 SAMBAS - Uci Sulistiarini; Hairida Hairida; Fitriani Fitriani (Universitas Muhammadiyah Pontianak, 2017)
ABSTRACTThis study aimed to find out students’ communication skills after using cooperative learning model type pair checks and by lecturing and discussion method, to know the difference of students’ learning results after using cooperative learning model type pair checks and by lecturing and discussion method, and also to know the effectiveness of usng cooperative learning model type pair checks. It is a quasi experimental. Research used simple random sampling technique in taking the sample. The analysis of students learning results reported that the mean of students in experimental class 86,94 % is higher than the mean of students in control class 64,30 %. The analysis of students communication skills results reported that the percentage of students communication skills in experimental class 84% is higher than the percentage of students’ communication skills in control class 65%. The result of statistic test with α = 5 % the value is 0,00 which is lower than α (0,00<0,005). It means that there are some differences between esperimental class and control class. Effect size showed ES = 1,22 categorized as high, which means that cooperative learning model type pair checks affect significantly to students’ learning results as 38,69%.Keywords: Learning results, communication skills, Solubility and Solubility Product, Type of Pair Checks